2022
DOI: 10.1186/s12864-022-08351-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic testing of dogs predicts problem behaviors in clinical and nonclinical samples

Abstract: Background Very little is known about the etiology of personality and psychiatric disorders. Because the core neurobiology of many such traits is evolutionarily conserved, dogs present a powerful model. We previously reported genome scans of breed averages of ten traits related to fear, anxiety, aggression and social behavior in multiple cohorts of pedigree dogs. As a second phase of that discovery, here we tested the ability of markers at 13 of those loci to predict canine behavior in a commun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…Various studies have been conducted on behavioral problems in dogs of different sizes, and they have found that small dogs with similar genetic markers and brain sizes tend to exhibit more behavioral disorders. (22,24) Previous research has classified these breeds as belonging to similar categories and possessing similar behavioral repertoires. For instance, Chihuahua and Poodle have been identified as non-working dogs that exhibit higher levels of direct social fear, as assessed by the C-BARK.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies have been conducted on behavioral problems in dogs of different sizes, and they have found that small dogs with similar genetic markers and brain sizes tend to exhibit more behavioral disorders. (22,24) Previous research has classified these breeds as belonging to similar categories and possessing similar behavioral repertoires. For instance, Chihuahua and Poodle have been identified as non-working dogs that exhibit higher levels of direct social fear, as assessed by the C-BARK.…”
Section: Discussionmentioning
confidence: 99%
“…(20) In general, a dog's body size can predict variations in its behavioral traits, such as aggression, anxiety, and trainability. (21,22) For example, small breeds tend to exhibit behavioral issues more frequently, (23) whereas larger breeds display a greater inclination towards training. (22,24) Another source of variation in behavior and body language between dogs is the sex and age of the individual.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, strong positive correlation was found between all the components of C‐BARQ questionnaire (Hsu & Serpell, 2003) related to aggression and fear (stranger‐, owner‐, dog‐ and familiar dog‐directed aggression, stranger‐directed, dog‐directed and non‐social fear) and veterinary behavioural diagnoses in 122 dogs (Zapata et al, 2022). Moreover, several genetic loci have been shown to have a significant association with these behavioural traits (Zapata et al, 2016) and could correctly predict individual behaviour in a cohort of nearly 400 pure‐ and mixed‐breed dogs, while a subset of those loci could predict veterinary behavioural diagnoses (Zapata et al, 2022). This demonstrates that owner‐assessed behavioural traits can have a strong genetic component and may serve as good predictors of individual behavioural problems.…”
Section: Discussionmentioning
confidence: 99%
“…The instrument’s various scales have been shown to have adequate internal reliability and acceptable test-retest and inter-rater reliability 22 24 . Construct and criterion validity of the C-BARQ have been established by demonstrating associations with: (a) clinical diagnoses of behavior problems in companion dogs 19 , (b) training outcomes in working dogs 15 , 22 , 25 , (c) the behavior of dogs in standardized test batteries 16 , 26 31 , (d) neurophysiological markers of canine anxiety disorders 32 , 33 , and (e) genetic loci known to be associated with the brain and behavior 34 36 .…”
Section: Introductionmentioning
confidence: 99%